Adapting Alternative Learning Resources to Diverse Learning Styles in Accounting Education for Adult Leaners - Dewi, Aprilia Cintya (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study explores how alternative learning resources can be tailored to diverse learning styles in accounting education for university level. It investigates the alignment between students’ learning preferences—visual, auditory, reading/writing, and kinesthetic—and the resources they find most effective. Through surveys and interviews, the findings suggests that students benefit from a wide range of learning materials, such as multimedia tutorials, podcasts, textbooks, and interactive simulations. Blended learning approaches, which combine traditional and digital resources, are proven to effectively support different learning styles. These findings emphasize the importance of providing accessible, flexible, and diverse learning materials to improve student engagement and academic performance. Additionally, the study addresses challenges related to digital access and the role of educators in fostering an inclusive learning environment. overall, this research underscores the need for adaptive teaching strategies to varied learning needs of accounting students in higher education.